X-ray and Infrared Microanalyses of Mona Lisa's Ground Layer and Significance Regarding Leonardo da Vinci's Palette - Gonzalez, Victor; Wallez, Gilles; Ravaud, Elisabeth; Eveno, Myriam; Fazlic, Ida; Fabris, Tiphaine; Nevin, Austin; Calligaro, Thomas; Menu, Michel; Delieuvin, Vincent; Cotte, Marine (Journal of the American Chemical Society, 2023)
An exceptional microsample from the ground layer of Leonardo da Vinci's Mona Lisa was analyzed by high-angular resolution synchrotron X-ray diffraction and micro Fourier transform infrared spectroscopy, revealing a singular mixture of strongly saponified oil with high lead content and a cerussite (PbCO3)-depleted lead white pigment. The most remarkable signature in the sample is the presence of plumbonacrite (Pb5(CO3)3O(OH)2), a rare compound that is stable only in an alkaline environment. Leonardo probably endeavored to prepare a thick paint suitable for covering the wooden panel of the Mona Lisa by treating the oil with a high load of lead II oxide, PbO. The review of Leonardo's manuscripts (original and latter translation) to track the mention of PbO gives ambiguous information. Conversely, the analysis of fragments from the Last Supper confirms that not only PbO was part of Leonardo's palette, through the detection of both litharge (α-PbO) and massicot (β-PbO) but also plumbonacrite and shannonite (Pb2OCO3), the latter phase being detected for the first time in a historical painting.An exceptional microsample from the ground layer of Leonardo da Vinci's Mona Lisa was analyzed by high-angular resolution synchrotron X-ray diffraction and micro Fourier transform infrared spectroscopy, revealing a singular mixture of strongly saponified oil with high lead content and a cerussite (PbCO3)-depleted lead white pigment. The most remarkable signature in the sample is the presence of plumbonacrite (Pb5(CO3)3O(OH)2), a rare compound that is stable only in an alkaline environment. Leonardo probably endeavored to prepare a thick paint suitable for covering the wooden panel of the Mona Lisa by treating the oil with a high load of lead II oxide, PbO. The review of Leonardo's manuscripts (original and latter translation) to track the mention of PbO gives ambiguous information. Conversely, the analysis of fragments from the Last Supper confirms that not only PbO was part of Leonardo's palette, through the detection of both litharge (α-PbO) and massicot (β-PbO) but also plumbonacrite and shannonite (Pb2OCO3), the latter phase being detected for the first time in a historical painting.